POLA PERTUMBUHAN BERDASARKAN BERAT DAN TINGGI BADAN SISWA PADA SEKOLAH NEGERI DAN SWASTA DI KOTA DENPASAR, BALI - DAMAYANTI, IDA AYU MANIK; JUNITHA, I KETUT; SUASKARA, IDA BAGUS MADE (Jurnal Biologi Udayana; Vol 21 No 2 (2017): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2017.vol21.i02.p06, 2017)
This research aimedet al. to determine the pattern of growth in several primary schools and secondary public and private schools in Denpasar, Bali Province. Samples were determined using purposive sampling and data were collected by cross-sectional method. The pattern of growth of boys and girls at the age of 7-15 years at private schools in Denpasar shows that the average height and weight were greater than the boys and girls in public schools in Denpasar. The percentage of underweight category was higher at public school in Denpasar and the percentage of children with overweight and obese categories were higher in the private national plus school Denpasar.